Addressing human trafficking in the context of gender-based violence: legal insights - Grīnfelde, Annija Katrīna (Riga Graduate School of Law, 2024)
This thesis explores the complex connection between human trafficking and gender-based violence within the European Union, as well as the legal frameworks that have been established to tackle these issues. Through doctrinal legal research the thesis focuses on the effects of gender-based violence on victims of human trafficking, while acknowledging the disproportionate impact on women and girls. The thesis highlights the shortcomings of legal systems such as inadequate victim protection and procedural mistakes, further advocating for greater global collaboration, victim assistance, societal awareness, protection of vulnerable groups, and gender-sensitive laws and policies. The findings suggest that gender-based violence and the psychological effects of it makes women and girls more vulnerable to manipulation and exploitation by traffickers. Thus, the 1949 UN Convention, the Palermo Protocol, Directive 2011/36/EU, CEDAW, and the Istanbul Convention are especially significant and time to time amendment to successfully address these matters.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law; human trafficking; gender-based violence; The European Union